Perkembangan perkamusan Melayu: suatu analisis dari sudut tipologi formal (Jurnal Bahasa, 2004)
The classification of dictionaries based on formal features indicate that the development of Malay dictionaries is on a par with the western dictionaries tradition. Several types of dictionaries had been published such as comprehensive dictionaries, abridged dictionaries edition and pocket size dictionaries. The metalanguage of the dictionaries encompassing general and specialized aspects. Most of the dictionaries are compiled in alphabetical or thematic order. Since Pigafetta dictionary printed in the 15th century, the Malay dictionaries encountered transformation with the existence of the multimedia and the electronic dictionary such as Kamus Komputer Telapak Besta DBP-1. The dictionaries compilation are to cater for the codifying and decoding purposes, depend on the dictionaries users. Each of the dictionary compiled have their own information category which differ from other genre. The most significance in the world of Malay dictionaries tradition is the capability of the Malay language as an object language either in monolingual, bilingual or multilingual. This contributed in elevating the Malay dictionaries tradition which is on a par with the western dictionaries development.